Barn og unge By, sted og sosiomaterialitet - Evenstad, Randi; Knut Greve, Anne; Seim, Sissel; Bekken, Wenche; Ekne Ruud, Marit; Kristensen, Olav; Andersen, Bengt; Opsahl, Kari; Sæter, Oddrun; Andreassen Becher, Aslaug; Rossholt, Nina (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"What are the conditions children and young people experience in the city? What opportunities does the city provide for interaction between people and urban spaces and places? What sociomaterial conditions for participation exist in institutions for children and young people? Can urban spaces, places and sociomateriality function in unexpected ways for children and young people? The topic of this book is the interaction between people and spaces, places and sociomateriality. The authors focus on the city as an object and as a context for children and young people growing up and engaging in play and activities. In addition, sociomaterial conditions in institutions for children and adolescents (daycare centres, schools and child protection services), as well as their interaction with professionals, are also analysed. This anthology includes eleven peer-reviewed academic chapters. The authors are researchers at OsloMet - Oslo Metropolitan University - in social and health studies, preschool teacher studies, the aesthetic disciplines and at the Centre for Welfare and Labour Research (SVA), the university's institute for commissioned research. The book will be of interest to all those concerned with the conditions of children and young people and the interaction between human agency and its material context in cities and institutions for children and adolescents: researchers, staff and students in social and health studies and teacher training programmes, as well as practitioners."